Impact of Organization Politics on Human Resource Management Practices and Employee Performance - Rehana Yasmeen; Munaza Bibi; Ali Raza (SEISENSE (PRIVATE) LIMITED, 2019)
Purpose- The purpose of this study was to investigate the impact of nepotism & favoritism as a form of organization politics on HRM practices and employee performance. Design/Methodology- Explanatory research design was employed to determine the effect of nepotism & favoritism on HRM practices and employee performance. Primary data collection method was used among employees working in different public-sector hospitals based on their accessibility. For this study, the sample of 150 employees was used. The adapted questionnaire was used for data collection. Data were analyzed using SPSS. Findings- The correlation analysis revealed a significant relationship between favoritism, employee performance & HRM practices whereas nepotism has a significant association with employee performance but the insignificant relationship with HRM practices. The outcomes of the study unveiled a significantly negative effect of nepotism on employee performance & HRM practices while favoritism has a significantly positive effect on employee performance & HRM practices. Practical Implications- The study outcomes might help public sector hospitals HR department to incorporate some changes regarding their policies to prevent the nepotistic & favoritism practices which can lead to creating a politics in the organization in which everyone works to fulfill his or her self- interest without focusing towards organizational goals achievement.